Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1152/ajpendo.00508.2004
|View full text |Cite
|
Sign up to set email alerts
|

Acute hypoxia decreases plasma VEGF concentration in healthy humans

Abstract: Vascular endothelial growth factor (VEGF) is known to be upregulated by hypoxia in vitro. However, in vivo data about VEGF regulation in chronic hypoxic diseases are conflicting. We investigated the effects of hypoxia on plasma VEGF concentration in healthy subjects. To control known confounders, such as insulin, glucose concentrations, or exercise, hypoxic effects on VEGF were studied during experimentally clamping glucose concentrations at rest. In a double-blind crossover study design, we induced hypoxia fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 50 publications
3
32
2
2
Order By: Relevance
“…Results from the hypoglycemic intervention are consistent with previous investigations demonstrating an increase of circulating VEGF concentrations upon blood glucose drop in humans [11][12][13], although data from the present study failed to reach significance probably because of the short period of blood sampling after induction of hypoglycemia. In contrast, brief hyperglycemia clearly decreases circulating VEGF concentrations.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Results from the hypoglycemic intervention are consistent with previous investigations demonstrating an increase of circulating VEGF concentrations upon blood glucose drop in humans [11][12][13], although data from the present study failed to reach significance probably because of the short period of blood sampling after induction of hypoglycemia. In contrast, brief hyperglycemia clearly decreases circulating VEGF concentrations.…”
Section: Discussionsupporting
confidence: 90%
“…Although it was previously found in accordance with in vitro data that hypoglycemia induces a rapid increase in circulating VEGF concentrations in humans [11][12][13], our group could also demonstrate that, contrasting to in vitro investigations, acute hypoxia decreases plasma VEGF concentrations in healthy men [13]. It has been postulated that high glucose concentrations induce a pseudohypoxic state because of a high NADH + /NAD + ratio in cells even when the oxygen tension is normal [14].…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the effect of the length of the training and the length of propensity for altered responses after training has yet to be determined. However, the effects on epinephrine are likely a consequence of both the hyperventilation phase and hypoxia due to breath retention, as both have been demonstrated to increase epinephrine levels (18,(21)(22)(23)(24). The hyperventilation-induced increase in epinephrine was shown to be dependent on decreased levels of bicarbonate, as hyperventilation combined with bicarbonate infusion (resulting in hypocapnia and alkalosis, but normal bicarbonate levels) nullified epinephrine increase (24).…”
Section: Discussionmentioning
confidence: 99%
“…However, for VEGF this is not necessarily the case. While there is clear evidence in cell culture to show that hypoxia induces an increase in the expression of VEGF (Ferrara, 2004), nevertheless Oltmanns et al (2006) found that acute systemic hypoxia may decrease circulating VEGF levels. Furthermore, a recent study has demonstrated that substantial temporal dissociation between mRNA and protein levels may occur for VEGF in the skeletal muscle of rats (Milkiewicz et al 2006).…”
Section: Exp Physiol 931 Pp 104-114mentioning
confidence: 97%